PROCESS-BASED FLIPPED CLASSROOM IN THE TEACHING OF ESL WRITING - Uswatun Nurrahmah Noorhassanah; Wardatul Akmam Din; Megawati Soekarno; Suyansah Swanto, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The English language is one of the most important language in the world the fact that it is considered as a universal language by the fact that how much it is used in peoples communication accord the world. Not everyone in the world certainly speaks fluently in English, but the fact that it is widely used wherever we are whether locally or even travelling in the foreign countries. Out of the four skills of language acquiring writing skill is undeniably the hardest skill to be taught and learnt in classroom with a short time constraint in a school day, which is one of the reasons that it is always to be given as a homework for students to do at their home. However, the writing product written by learner is fairly disappointing and does not seem to correlate with their abilities in some other language abilities. Thus, this paper will be discussing about Flipped Classroom Approach and Process-based Approach would help in enhancing students writing performance respectively. This SLR paper are using few inclusions in order to retrieve related articles using the right keywords. At the end of this paper, authors will proposed a combination of the two approaches using the post-method pedagogy.